SISTEM PENUNJANG KEPUTUSAN PENERIMAAN PEGAWAI STUDIO RISA BEAUTY BALI DENGAN METODE SAW - Kadek Ayu Puspita Dewi; A. Sidiq Purnomo (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Employees are one of the important assets owned by the company in its efforts to maintain business continuity, business development and for the ability to compete for profit. In order to get qualified employees and in accordance with the criteria desired by Studio Risa Beauty Bali, a decision support system (SPK) is used that can facilitate decision making to determine optional using criteria and the Simple Additive Weighting (SAW) method is a problem-solving solution in employee recruitment. The Simple Additive Weighting (SAW) method was chosen because it can determine the weight value for each criterion, then proceed with the ranking process which will select the best alternative from each existing alternative. In this case, the alternative in question is the determination of employee recruitment for Studio Risa Beauty Bali. With this ranking method, it is expected that the assessment will be more precise because it is based on predetermined criteria and weight values so that it will get maximum results